2004
DOI: 10.1111/j.0013-0427.2004.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cost Differentials between Public and Private Enterprises: A Mixed Duopoly Approach

Abstract: We investigate a mixed duopoly, where a state-owned welfare-maximizing public firm competes against a profit-maximizing private firm. We use a Hotelling-type spatial model which represents product differentiation. We endogenize production costs by introducing cost-reducing activities. We show that the private firm's cost becomes lower than the public firm's because the private firm engages in excessive strategic cost-reducing activities. Even though each firm's cost is heterogeneous, the locations of the firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 37 publications
2
120
2
Order By: Relevance
“…In addition, Martin and Parker (1997) suggested that corporate performance can either increase or decrease after privatization, based on their study in the United Kingdom. See Matsumura and Matsushima (2004) for a theoretical discussion of the endogenous cost differences between public and private enterprises.…”
Section: Modelmentioning
confidence: 99%
“…In addition, Martin and Parker (1997) suggested that corporate performance can either increase or decrease after privatization, based on their study in the United Kingdom. See Matsumura and Matsushima (2004) for a theoretical discussion of the endogenous cost differences between public and private enterprises.…”
Section: Modelmentioning
confidence: 99%
“…As shown in Matsumura and Matsushima (2004), when both firms maximize their profits, they choose excessive R&D investment to gain competitive advantages in the following location-pricing game. The equilibrium results are as follows: …”
Section: Lemma 2 (No Privatization) When One Public Firm Competes Agamentioning
confidence: 99%
“…And if a private investor wants to start her own gas station, she chooses the location of the station and the retail price of the gasoline, but buys the gasoline from CNPC or Sinopec (another public firm in China). 6 It has been found that in the Hotelling model, the existence of a public firm can guarantee the social optimal location and pricing equilibrium under various settings like symmetric costs (Cremer, Marchand, and Thisse 1991), asymmetric costs (Matsumura and Matsushima 2004), and with subcontracting between firms (Shuai 2016). Thus any kind of privatization of the retailer reduces the social welfare.…”
Section: Propositionmentioning
confidence: 99%
See 2 more Smart Citations